INFLUENCE OF FIRMS SIZE, EXCHANGE RATE, PROFITABILITY AND TAX BURDEN ON TRANSFER PRICING - Nurwati Nurwati; Prastio Prastio; Nawang Kalbuana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to analyze the effect of Firm Size, Exchange Rate, Profitability, and Tax Burden on Transfer Pricing on Automotive Manufacturing Companies and Components Registered on the Stock Exchange for the 2014-2018 Period in partial or simultaneous periods. The sampling technique in this study used a purposive sampling method by establishing several sample criteria. Of all listed companies, there are only 7 companies that meet the sample criteria in this study with a study period of 5 years so as to produce a sample of 35 samples. Data processing is performed using test equipment contained in SPSS. Testing the influence of variables on the F test shows the results of sig. 0.010 0.05 then Ho is accepted and Ha is rejected, which means that Firm Size has no significant effect, the Exchange Rate shows the results of 0.515> 0.05 then Ho is accepted and Ha is rejected, which means Excange Rate no significant effect, the profitability shows the results 0.003